Clinical and anatomical myocardium features according to invasive and non-invasive examination methods in patients with coronary artery disease in combination with diabetes mellitus - M. B. Buzurtanova; R. T. Didigova; Z. O. Ugurchieva; B. U. Mardanov; M. N. Mamedov (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To study the clinical and anatomical myocardium features according to invasive and non-invasive examination methods in men and women with coronary artery disease (CAD) in combination with diabetes mellitus (DM).Material and methods. A single-step clinical study included 77 men and 68 women with angina of the II-III functional classes, observed in the Republican clinical hospital in Nazran. Depending on the presence of type 2 DM and gender, patients were divided into 4 groups: Group I — men with CAD+DM (n=34), Group II — women with CAD+DM (n=36), Group III — men with CAD without DM (n=43), group IV — women with CAD without DM (n=32). All patients underwent electrocardiography (ECG), echocardiography (EchoCG) and coronary angiography.Results. Hypertrophy of the left ventricle on ECG was most often diagnosed in men with CAD+DM (38%). Similar, but less pronounced tendency is observed in men without DM (23%). Among women, these parameters were <20%. Left ventricular hypertrophy on EchoCG was determined two times more than the ECG results. Defect of local contractility and myocardial hypokinesis according to EchoCG data was found in both men and women with DM — 29% and 22%, respectively. Among patients without DM, these parameters were 40% less. In general, the frequency of cicatricial ECG changes in all groups had a similar trend. According to coronary angiography, anterior interventricular stenosis was the most frequent vascular lesion. Among men with CAD+DM, it was noted in 62% of cases, in men without DM — in 30%. Among women with CAD+DM, anterior interventricular branch stenosis is detected in 28% of cases, without ~20%. Stenosis of the circumflex branch is detected in no more than 20% of cases in men and women with CAD+DM, and in the groups without DM — in 10%. Stenosis of the right coronary artery is detected in every fourth patient, regardless of the glycemic status. The majority of patients (60%) have constriction of the coronary vessels, the absolute number of such constrictions in the groups of men with CAD and with or without DM was ~70 cases. Among women, this figure was less than 50 cases. Constriction of one or more coronary arteries >80% more often occurred among men with CAD without DM, among men and women with CAD+DM, the absolute number of such constrictions was 21-25 cases. The greatest number of stenoses ≥2 coronary arteries was observed in men with CAD+DM (~30 cases), in the group of men with CAD without DM constriction >2 vessels are found in ~20 cases. Among women, stenosis ≥2 vessels are detected twice as less as compared with men. At the same time, in the group of women with CAD+DM, the frequency of multiple stenoses was 15% higher than those of women with CAD without DM.Conclusion. Thus, using non-invasive and invasive examination methods in CAD patients, a number of complementary changes in the myocardium and coronary arteries were found. The presence of DM worsens these changes, both among men and women.